2002
DOI: 10.1038/sj.tpj.6500089
|View full text |Cite
|
Sign up to set email alerts
|

Human sulfotransferase SULT2A1 pharmacogenetics: genotype-to-phenotype studies

Abstract: SULT2A1 catalyzes the sulfate conjugation of dehydroepiandrosterone (DHEA) as well as other steroids. As a step toward pharmacogenetic studies, we have 'resequenced' SULT2A1 using 60 DNA samples from African-American and 60 samples from Caucasian-American subjects. All exons, splice junctions and approximately 370 bp located 5' of the site of transcription initiation were sequenced. We observed 15 single nucleotide polymorphisms (SNPs), including three non-synonymous coding SNPs (cSNPs) that were present only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 38 publications
5
68
1
Order By: Relevance
“…The frequencies of the G187C and G781A variants in the AR and AL populations were similar to those reported by Thomae et al (2002). The presence of the G187C and G781A variants are tightly linked giving rise to essentially three haplotypes.…”
Section: Sult2a1supporting
confidence: 84%
See 2 more Smart Citations
“…The frequencies of the G187C and G781A variants in the AR and AL populations were similar to those reported by Thomae et al (2002). The presence of the G187C and G781A variants are tightly linked giving rise to essentially three haplotypes.…”
Section: Sult2a1supporting
confidence: 84%
“…Thomae et al (2002) have reported the resequencing and analysis of sequence variants in the SULT2A1 gene of 60 Caucasian and African-Americans (AA) DNA samples obtained from the Coriell Cell Repository. A total of 15 SNPs were identified in the 5 0 -flanking region and intron and exon sequences of the SULT2A1 gene sequenced.…”
Section: Sult2a1mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Figure 4 show that there was a highly significant correlation between level of enzyme activity and quantity of immunoreactive protein in these variant allozymes -ranging from high values for the WT sequence to virtually no protein for TPMT*3A . This phenomenon has also been observed for many other common genetic polymorphisms that alter only a single amino acid (Freimuth et al, 2001;Thomae et al, 2002;Adjei et al, 2003;Thomae et al, 2003;Weinshilboum and Wang, 2004a;Ji et al, 2005). Of the allozymes studied by Salavaggione et al (2005), TPMT*3A, *3B, *3C and *2 displayed the most striking effects.…”
Section: Tpmt: Functional Genomics and Molecular Mechanismsmentioning
confidence: 55%
“…[31][32][33] More recently, a series of gene resequencing and functional genomic studies have resulted in the identification of functionally significant genetic polymorphisms for SULT1A1, 34 SULT1A3, 35 SULT1E1, 36 and SULT2A1. 37 One of the SULT1A1 polymorphisms has already been reported to be of pharmacogenetic significance for variation in the survival of breast cancer patients treated with tamoxifen. 38 Therefore, it is important for pharmacogenetics that all human genes encoding cytosolic SULTs be identified and characterized.…”
Section: Rr Freimuth Et Almentioning
confidence: 99%